Recurrent back pain of unknown etiology - suspect an urological origin! - Paula Nunes (Pediatric Urology Case Reports, 2016)
Ureteropelvic junction (UPJ) obstruction poses a diagnostic challenge when the patient arrives at the emergency department with severe recurrent back pain without previous record of this condition. Extrinsic factors including crossing vessels or intrinsic factors such as adynamic segment of proximal ureter can cause UPJ obstruction. We report a case of a 16 year-old female patient with ureteropelvic junction syndrome occurring at adolescence, caused by two accessory vessels. She was submitted to a laparoscopic dismembered pyeloplasty with favorable outcome.